Historical aspects of medical and pedagogical supervisions of training process in athletes and sportsmen (literature Review) - Михалюк [Mikhalyk Ye.], Євген Леонідович (Slobozhanskyi Herald of Science and Sport, 2012)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--> Through monitoring stages of improving medical and pedagogical supervisions of athletes in history. The data on the research with additional and specific repeat physically demanding in athletes of different sports. Carefully consider the conduct of medical and pedagogical supervisions through the use of telemetric pulse remote sensor of «Polar» system in combat sports athletes. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->